Hot, fancy, and dangerous: The representation of female characters in three popular video games: Multimodal discourse analysis - Muhammad Hafiz Kurniawan; Wawan Gunawan; Dadang Sudana (EduLite: Journal of English Education, Literature and Culture, 2023)
A video game is one of the popular cultures that gained much popularity among teenagers and adults. However, with its popularity, it also has controversy where female characters in video games are frequently to satisfy a male fantasy. Therefore, this research aims to investigate the representation of female characters in three video games: Metal Gear Solid V: The Phantom Pain, Mark of The Ninja, and Naruto Shippuden: Ultimate Ninja Storm 4. This research aims to address how the representation of female characters also portrays that sexism in video games still lingers. This research applied multimodal discourse analysis inspired by Haliday’s Social Semiotics. This research also uses Kress and van Leeuwen’s techniques in analysing visual semiotic sources. This research used four steps of collecting and analysing data proposed by Bezemer and Jewitt collecting and logging data, viewing, sampling data, and transcribing and analysing data. In the collecting and logging data phase, this research collected recorded gameplay and videogame cut scene using Bandicam software and took notes from semiotic sources representing the female characters. Viewing and sampling data involved the viewing process in the recorded video and taking a sample of data from four female characters. After that, the researcher transcribes and analyses the data using a multimodal discourse analysis framework. This research found that those first lead female characters are represented by wearing tight and obscene attire but having skills in influencing the main character.